2006
DOI: 10.1111/j.1365-2133.2006.07340.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical methyl aminolaevulinate photodynamic therapy for treatment of facial acne vulgaris: results of a randomized, controlled study

Abstract: MAL-PDT is effective in the treatment of moderate to severe inflammatory facial acne. Further studies are warranted to optimize this promising procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 26 publications
6
88
1
Order By: Relevance
“…MAL-PDT has antimicrobial effects and can eliminate members of the Malassezia species. The mode of action of these observed effects is not totally clear; however, these effects may be the result of either acting as a local immunomodulant, inhibiting growth via activation of endogenous porphyrins, and/or initiating photodynamic destruction of pilosebacous units [18][19][20]. Upon exposure to light, protoporphyrin IX (PpIX) induces cytotoxic effects through oxygen-dependent photochemical reactions that damage mainly the mitochondria, where PpIX is synthesized, and plasma membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAL-PDT has antimicrobial effects and can eliminate members of the Malassezia species. The mode of action of these observed effects is not totally clear; however, these effects may be the result of either acting as a local immunomodulant, inhibiting growth via activation of endogenous porphyrins, and/or initiating photodynamic destruction of pilosebacous units [18][19][20]. Upon exposure to light, protoporphyrin IX (PpIX) induces cytotoxic effects through oxygen-dependent photochemical reactions that damage mainly the mitochondria, where PpIX is synthesized, and plasma membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this study, we attempted to treat recalcitrant Malassezia folliculitis with MAL-PDT. We chose to use MAL as the photosensitizer in this study because, compared with ALA, MAL has enhanced lipophilicity and should therefore be more effective than ALA for treating disorders of the pilosebaceous unit and fungus [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, almost 16 years have passed since the first studies on ALA-PDT in acne therapy; there is still no consensus on how to perform PDT for acne treatment, and its use still remains an off-label option for acne patients [22] . Despite numerous studies on PDT in acne (mainly mild to severe acne on the face but also acne lesions on the back and acne conglobata) [1,18,20,21,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] ( Table 1 ), they are generally difficult to compare because of the lack of controls, qualitative non-blinded methods, variable light dosimetry, and an extremely wide variation of the incubation time between drug application and light exposure. All these differences should not be neglected.…”
Section: Acnementioning
confidence: 99%
“…All of the subjects experienced moderate to severe pain during illumination, and developed erythema, pustular eruptions, and epithelial exfoliation after treatment, which were more severe and uniform in the ALA-PDT-treated area. Another randomized controlled split-face study of MAL-PDT using red light also showed a 54% reduction of inflammatory lesions with significant side effects of pain and erythema [21]. Robust prospective, randomized, controlled trials in the areas of light-based therapy or photodynamic therapy for acne are limited.…”
Section: Discussionmentioning
confidence: 99%